Protection From Apoptotic Cell Death During Cold Storage Followed by Rewarming in 13-Lined Ground Squirrel Tubular Cells: The Role of Prosurvival Factors X-Linked Inhibitor of Apoptosis and PhosphoAkt. Issue 3 (March 2016) - Jain, Swati; Keys, Daniel; Martin, Sandra; Edelstein, Charles L.; Jani, Alkesh
Abstract : Background: Hibernators, such as the 13-lined ground squirrel, endure severe hypothermia during torpor followed by periodic rewarming (REW) during interbout arousal (IBA), proapoptotic conditions that are lethal to nonhibernating mammals. We have previously shown that 13-lined ground squirrel tubular cells are protected from apoptotic cell death during IBA. To understand the mechanism of protection, we developed an in vitro model of prolonged cold storage (CS) followed by REW, which is akin to the in vivo changes of hypothermia followed by REW observed during IBA. We hypothesized that renal tubular epithelial cells (RTECs) isolated from hibernating ground squirrels would be protected against apoptosis during CS/REW versus nonhibernating mouse RTECs. Methods: Isolated hibernating ground squirrel and mouse RTECs were subjected to CS at 4°C for 24 hours followed by REW to 37°C for 24 hours (CS/REW). Results: Ground squirrel RTECs had significantly less apoptosis compared to mouse RTECs when subjected to CS/REW. Next, we hypothesized that the mechanism of protection was related to the antiapoptotic proteins X-linked inhibitor of apoptosis (XIAP), phospho-Akt (pAkt), and phospho-BAD. There was a significantly increased pAkt and pBAD expression in ground squirrel versus mouse RTECs subjected to CS/REW. The XIAP expression was maintained in ground squirrel RTECs but was significantly decreased in mouse RTECs after CS/REW. Ground squirrel RTECs in which gene expression of Akt1 and XIAP was silenced lost their protection and demonstrated increased apoptosis and cleaved caspase-3 expression after CS/REW. Conclusions: Our findings suggest that ground squirrel RTECs are protected against apoptosis during prolonged CS/REW by the "prosurvival" factors XIAP and pAkt. Abstract : Hypothermia followed by rewarming is pro-apoptotic for nonhibernating mammals. Renal tubular epithelial cells from hibernating squirrels are more resistant than mouse cells to apoptosis after hypothermia followed by rewarming. This resistance is dependent on Akt1 and XIAP. This model allows identifying therapeutic targets to improve organ preservation, and prevents delayed graft function.